Business consulting para la empresa ME consultoría y comunicaciones S.A.C. - Zapata Vera, Jonathan (2025)
This research focused on the overall situation of ME Consultoría y Comunicaciones S.A.C. ("Why Not?") and its performance in the competitive digital advertising market in Peru. Since its founding in 2019, the company has grown through a creative approach and diversification in its services; however, it faces significant challenges, such as inadequate financial management, lack of qualified personnel, and an unfavorable work environment. Given this, using methodologies such as Design Thinking, it was identified that the lack of financial experience among leaders limited strategic decision-making. The cause analysis, carried out using the Ishikawa Diagram and the prioritization matrix, highlighted critical problems such as the lack of follow-up to financial reports and the need for specialized personnel. Various solutions were proposed, prioritizing the hiring of an external team and a Process Analyst. Given this, an implementation plan was developed with key activities, schedule, and budget. The expected results include both qualitative and quantitative improvements, highlighting greater operational efficiency and an increase in profitability. In view of this, the economic free cash flow obtained was S/ 8,237.58, an economic IRR of 28%, an economic B/C of 1.17 and an economic PR of 1.88. Likewise, the financial cash flow obtained was a financial NPV of S/ 7,414.90, a financial IRR of 35%, a financial B/C of 1.20 and a financial PR of 2.29. All of these data together show that the project is profitable and will bring economic benefits to the company.